SOIL CARBON STOCKS IN SARAWAK, MALAYSIA - Padmanabhan, Eswaran (2010)
The relationship between greenhouse gas emission and climate change has led to research to identify and manage the natural sources and sinks of the gases. CO2, CH4, and N20 have an anthropic source and of these CO2 is the least effective in trapping long wave radiation. Soil carbon sequestration can best be described as a process of removing carbon dioxide from the atmosphere and relocating into soils in a form that is not readily released back into the atmosphere. Noted benefits of soil carbon sequestration include conservation of soil and water resources, improvement of the soil structure and off-setting emissions from fossil fuel combustion and other carbon emitting processes. The total global pool was estimated over a decade ago at about 41,000 Pg, of which the ocean reservoir contains about 38,000 Pg, the atmosphere about 750 Pg, and the terrestrial the remaining 2,100 Pg carbon. In the terrestrial system, soils contain about 1,500 Pg and vegetation, about 750 Pg carbon. The quantity and quality of soil organic matter depends on the soil and the environmental conditions. There is also a time element in the sequestration process. Soils on stable geomorphic surfaces subject to minimal erosion have the time to stock higher quantities of carbon. Soils on actively eroding surfaces are poor in carbon. Cold and wet conditions promote accumulation while in warm, well-drained soils, oxidation of carbon releases it to the atmosphere. It is reasonable to expect that under low input systems, there will be a continuous net loss of C from soils. Previous studies have shown that land clearing for agriculture results in 20 to 60% loss of the original soil C content. The purpose of this study is to estimate carbon stocks available under current conditions in Sarawak, Malaysia. SOC estimates are made for a standard depth of 100 cm unless the soil by definition is less than this depth, as in the case of lithic subgroups. Among the mineral soils, Inceptisols tend to generally have the highest carbon contents (about 25 kgm-2m-1), while Oxisols and Ultisols rate second (about 10-15 kgm-2m-1). The Oxisols store a good amount of carbon because of an appreciable time-frame to sequester carbon and possibly lower decomposition rates for the organic carbon that is found at 1m depths. Wet soils such as peatlands tend to store significant amounts of carbon. The highest values estimated for such soils are about 114 kgm-2m-1. Such appreciable amounts can also be found in the Aquepts. Human activities on the land are increasingly contributing to enhanced degradation of the carbon stocks. Oxisols and Ultisols are generally used for zero to low input agricultural systems by small holders. The same soils and also peat soils are now being used by the plantation sector to cultivate oil palm. In a properly managed agricultural scheme, degradation of the organic pool will be minimal. However, in considering soil resilience, specifically the resilience of organic carbon under varying management systems, it becomes apparent that the long-term sustainability of the organic pool could be questionable. Degradation will inevitable reduce the productivity of soils and thereby increasing more concerns on food stability. In conclusion, it is pertinent to recognize that degradation of the carbon pool, just like desertification, is a real process and that this irreversible process must be addressed immediately. Tension zones have to be identified perhaps even at the resource management domain levels. This would require more accurate soil maps to be produced at National, State, Provincial levels. Since it is known that the most widely used soils for agriculture also hold large reservoirs of carbon, it is stressed again that these soils also have the potential to sequester larger amounts. Therefore, appropriate soil management practices should be instituted to sequester large masses of soil carbon on an annual basis. Past estimates also show that wetlands hold about 30% of the total SOC. Therefore maintaining wetlands in their natural state is a good policy to enhance carbon sequestration. In retrospect, draining these wetlands tends to release CO2 into the atmosphere and it will be difficult to restore the original levels of SOC in a human time-span. Estimates have also shown that at the global level, forest soils stock about 580 Pg of SOC and about 360 Pg of above ground biomass carbon. This knowledge can be used effectively to formulate strategies to prevent forest fires and clearing: two processes that can quickly release sequestered carbon to the atmosphere in an almost irreversible manner.